Ethnomathematics Study at Pura Kerta Bhuwana Giri Wilis Nganjuk as a Context in Mathematics Learning Module - Uswah, Ali Huriya Harimatul; Surur, Agus Miftakus; Sulistyawati, Eka (Faculty of Tarbiyah, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2024)
Ethnomathematics is the study of mathematics from various cultural forms, allowing communities to discover and explore mathematical concepts within their culture. Cultural values of mathematics can be utilized in mathematics education. This research aims to identify the mathematical concepts found in Pura Kerta Bhuwana Giri Wilis Nganjuk and use them as components in preparing mathematics modules for seventh-grade junior high school students. Pura Kerta Bhuwana Giri Wilis is in the Loceret District of Nganjuk Regency. This temple has a strong traditional Javanese architectural style, featuring tiered roofs, relief decorations, and ornaments that symbolize Hindu beliefs. This research uses qualitative research with an ethnographic approach. Data collection through interviews was conducted to understand the history, philosophy, and components of Pura Kerta Bhuwana Giri Wilis Nganjuk. Observation and documentation were carried out to analyze the mathematical elements in the parts of the Pura. The research results show that Pura Kerta Bhuwana Giri Wilis contains mathematical concepts such as flat shapes (squares, rectangles, triangles, trapezoids, rhombuses), three-dimensional shapes (rectangular pyramids, rectangular prisms, cylinders), and geometric transformations (reflection and rotation). Using the Self-Directing Learning model, the mathematical concepts are then implemented into the Lesson Plan (RPP). The Self-Directing Learning model consists of three steps: Planning, Monitoring, and Evaluating. Ethnomathematics from Pura Kerta Bhuwana Giri Wilis are expected to enhance students' understanding of mathematics and develop learning media based on local culture.